A Reading of the Linguistic Output of Abdelrahman Hadj Salah: the “Linguistics Sciences Series” as a Model - bouguerfa, sabrina (El Omda in Linguistics and Discourse Analysis, 2024)
Abdelrahman Hadj Salah is an eminent scholar who has distinguished himself in the field of linguistic research thanks to his continuous scientific efforts and his prominent presence in various national and international intellectual and cultural conferences. His scholarly contributions have become one of the most important topics attracting the attention of Arab researchers and scholars, especially in recent years, through numerous academic and intellectual studies conducted in this field. His work has clearly revealed a significant shift in Arabic linguistics in terms of both methodology and technical approaches. Although this growing academic interest has raised several methodological and theoretical issues, there are still unanswered questions that require further investigation. Despite the importance of the studies conducted on his linguistic output, they remain insufficient in fully acknowledging his contribution. This reading focuses on the “Sciences of Language” series published by Abdelrahman Hadj Salah, which constitutes a coherent intellectual project characterized by unified references, general and specific hypotheses, as well as a distinctive critical practice.